Can conservation tillage and reduced irrigation promote sustainability in agroecosystems through lowering nitrous oxide emissions? A synthesis - Chen, Junjiang; Li, Guolin C.; Lee, Tien Ming; Veresoglou, Stavros D. (Plant and soil, 2024)
Background and Aims The agriculture sector is a major producer of greenhouse gases. To successfully transition to a green economy, we should further optimise agriculture practices so that we offset emissions while preserving crop productivity. We questioned here how two common organic management practices, reducing irrigation and conservation tillage as well as their interaction modify N 2 O emissions. Methods We synthesized across 265 studies and combined a series of linear models and a meta-analytical method of moments to analyze our data. Results We observed that reducing irrigation induced increases of about 66.1% in N 2 O emissions in rice but declines of over 17% for other crops, subject to mean annual temperature conditions. No tillage lowered N 2 O emissions, which was not the case for the reduced tillage practice. This resulted into the overall effect of conservation tillage practices on N 2 O emissions being non-significant. Conclusion We present evidence that managing N 2 O emissions from agroecosystems depends strongly on climatic conditions and crop type used. Mapping those dependencies facilitates budgeting greenhouse gas emissions from agroecosystems and smooths the path towards meeting sustainability targets in agriculture and horticulture.